Analysis Of Factors That Inhibit Early Reading Learning In Elementary School Students In Mis Al-Afkari Deliserdang - Junaidi, Junaidi; Pasaribu, Gumarpi Rahis; Siahaan, Annisa Frilisilia (Yayasan Insan Cipta Medan, 2023)
The purpose of this study was to describe the forms of difficulties faced by Class I students at MIS AL-Afkari Deliserdang that hindered early reading. This research is an observational study. Data collection techniques, using observation, interviews, and documentation. The data obtained were analyzed descriptively after being reduced (data reduction), and tested for validity through a data credibility test. The results showed that the types of difficulties faced by Class I students at MIS AL-Afkari Deliserdang that could potentially hinder learning to read the beginning were as follows: 1) students had difficulty reading the alphabet with proper pronunciation, students had difficulty showing and mentioning vowels, students had difficulty showing and mentioning consonants, students find it difficult to name some combined sounds of vowels and consonants, students find it difficult to spell the syllables that are instructed, 2) the factors that hinder students in Beginning Reading Difficulties in Class I students at MIS AL-Afkari Deliserdang are intellectual factors, factors physiological, environmental factors including parents, and psychological factors. The solution is that parents must really accompany their children when learning and teachers innovate in learning such as using suitable media and methods for learning to read early.